Development of Student Worksheets Based on the Nature of Science (NoS) on Chemical Bonds Topic - Fadilla, Aylinda Nurul; Herdini, Herdini; Holiwarni, Betty (Universitas Negeri Semarang, 2025)
The problem that is often experienced in learning chemical bonds topics is that students do not know the benefits of learning chemical bonds in everyday life, one of the causes is because the teaching materials used have not been able to link the material with contextual examples, real problems in everyday life, and the lack of opportunities for students to conduct investigations, making the learning less meaningful. This research aims to produce valid student worksheets based on the Nature of Science (NoS) on chemical bonds topics and determine user response. The research method used is Research and Development (R&D) using the 4-D development model (define, design, develop, and disseminate). The data collection instruments were validation sheets and user response questionnaires for teachers and students. The data analysis method in this research was carried out quantitative and qualitative data description. The results indicated that the developed student worksheets based on the Nature of Science (NoS) were deemed valid, with an average validation score of 96.12% from 3 validators. One-on-one trials were conducted with 3 students with different abilities to gather feedback for improvements. The user response test was conducted to 2 chemistry teachers and 20 students (10 students from SMAN 4 Pekanbaru and 10 students from SMAN 1 Pekanbaru), yielding response percentages of 90.06% from teachers and 90.84% from students, both categorized as very good. So, it can be said that these student worksheets have good potential to be used in learning chemistry, especially on topics related to chemical bonds.